Overcoming PARP Inhibitor and Platinum Resistance with WEE1 Inhibitors in Ovarian Cancer - Ilaria Colombo (healthbook TIMES. Oncology Hematology)
Poly (ADP-ribose) polymerase inhibitors (PARPi) have transformed the treatment of high-grade epithelial ovarian cancer (EOC), with demonstrated efficacy in the recurrent as well as newly diagnosed disease. However, women with EOC inevitably acquire resistance to both platinum chemotherapy and PARPi. Combining PARPi with agents targeting other DNA damage response (DDR) pathways to promote synthetic lethality is a rational therapeutic approach. Recent studies show that combination of PARPi and WEE1 inhibitors is feasible and might be an effective strategy for patients with platinum- and PARPi-resistant EOC. This article provides an overview of the latest preclinical and clinical trials evaluating WEE1 inhibitors in monotherapy or in combination with PARPi in advanced EOC.